(untitled) (Fiep Bulletin - online, 2016)
The aging process is characterized for many older people as the loss of autonomy and independence, increasing the long-term care homes sought. The objective of the study is to analyze the functional capacity and quality of life of the older people who reside in a condominium for elderly, pre and post physiotherapeutic intervention. A quantitative and qualitative longitudinal study in a Condominium for older people in the town ofCascavel was conducted in the period between May and July 2014, the sample consisted of 22 institutionalized elderly people and the pre and post physiotherapeutic intervention was evaluated with the Quality of Life questionnaire SF-36, and the functionality with the Barthel scale, beyond the socioeconomic status of the elderly. It was not observed statistically significant differences in the quality of life and functionality of the institutionalized older people, but it was observed clinical improvement in Barthel scale and in SF-36, specifically in the domains of functional capacity, physical limitations, pain, vitality and social aspects, inferring that physiotherapeutic activities change the states of functionality and quality of life of older people living in Long-term Care Homes.